Zuidelijk Afrika - Defillet, Wilfried; Verhaegen, Herwig; Velghe, Frank (Antwerpen: Jeugd en Derde Wereld, 1989)
"Wilfried Defillet; Herwig Verhaegen; Frank Velghe... et al. Themabrochure Scholierenparlement 1988-1989"